Interface Design of Quranic Application using Design Science Research Methodology: A Comparison of Gamification and Non-Gamification Design - Asidik Al Jafar; Margareta Hardiyanti; Rachmadita Andre Swari (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: To improve student motivation and engagement through an intuitive mobile interface with interactive visuals. Method: Using Design Science Research Methodology (DSRM), this study compares gamified and non-gamified interface designs. Results: User Experience Questionnaire (UEQ) results indicate that the gamified version outperforms the non-gamified design, particularly in stimulation and attractiveness, positively impacting learner and teacher satisfaction. Additionally, the Intrinsic Motivation Inventory (IMI) confirms that gamification significantly increases students' motivation, while the User Engagement Scale (UES) highlights the gamified version's effectiveness in creating an enjoyable, engaging, and impactful learning experience. Novelty: This research uniquely contrasts gamified and non-gamified designs in Quranic education, providing insights for quality improvement in Islamic e-learning platforms.